2021
DOI: 10.1093/ntr/ntab152
|View full text |Cite
|
Sign up to set email alerts
|

Vaping Disparities at the Intersection of Gender Identity and Race/Ethnicity in a Population-Based Sample of Adolescents

Abstract: Background Transgender adolescents use vape products (e.g., e-cigarettes) at higher rates than cisgender adolescents. Little is known about how these disparities differ from the intersectional perspective of both gender identity and race/ethnicity. Methods We examined disparities in past 30-day vaping frequency at the intersection of gender identity and race/ethnicity among adolescents participating in two pooled waves of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…It is worth mentioning that only 0.4% of our cohort did not disclose their race; as such, further studies are required to confirm the robustness of this finding. Still, these results are consistent with prior studies that demonstrated high perceived discrimination by youth to be associated with not only increased uptake of vaping but more frequent use as well [8,52]. Policies promoting cultural diversity, social inclusion, and integration coupled with incident recording and monitoring might mitigate discrimination and its consequences among adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…It is worth mentioning that only 0.4% of our cohort did not disclose their race; as such, further studies are required to confirm the robustness of this finding. Still, these results are consistent with prior studies that demonstrated high perceived discrimination by youth to be associated with not only increased uptake of vaping but more frequent use as well [8,52]. Policies promoting cultural diversity, social inclusion, and integration coupled with incident recording and monitoring might mitigate discrimination and its consequences among adolescents.…”
Section: Discussionsupporting
confidence: 90%
“…Although the vaping literature provides some knowledge on differences among vapers by gender or tobacco use status, there are two important gaps in this literature. First, the extent of the relationship between ENDS use, gender, and tobacco in the literature is confined to prevalence (32,33). Some studies have examined the odds of exposure to and engagement of youth to vaping-related content in social media but did not assess gender differences (34).…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings show that transgender adolescents of color are more likely to report higher frequency of vaping compared with cisgender white adolescents. Black transgender adolescents specifically, had six times the odds of more frequent vaping relative to their cisgender Black peers and nearly three times the odds of more frequent vaping relative to their transgender white peers [10 ▪ ]. Another study demonstrated that lesbian girls of color had a higher relative risk ratio of current e-cigarette use compared with both heterosexual girls of color and lesbian White girls.…”
Section: Recent Studies Using An Intersectional Frameworkmentioning
confidence: 97%